Balanced crystalloid solution versus saline in deceased donor kidney transplantation (BEST-Fluids): a pragmatic, double-blind, randomised, controlled trial - Collins, Michael G; Fahim, Magid A; Pascoe, Elaine M; Hawley, Carmel M; Johnson, David W; Varghese, Julie; Hickey, Laura E; Clayton, Philip A; Dansie, Kathryn B; McConnochie, Rachael C; Vergara, Liza A; Kiriwandeniya, Charani; et al. (The Lancet (British edition), 2023)
Delayed graft function (DGF) is a major adverse complication of deceased donor kidney transplantation. Intravenous fluids are routinely given to patients receiving a transplant to maintain intravascular volume and optimise graft function. Saline (0·9% sodium chloride) is widely used but might increase the risk of DGF due to its high chloride content. We aimed to test our hypothesis that using a balanced low-chloride crystalloid solution (Plasma-Lyte 148) instead of saline would reduce the incidence of DGF. BEST-Fluids was a pragmatic, registry-embedded, multicentre, double-blind, randomised, controlled trial at 16 hospitals in Australia and New Zealand. Adults and children of any age receiving a deceased donor kidney transplant were eligible; those receiving a multi-organ transplant or weighing less than 20 kg were excluded. Participants were randomly assigned (1:1) using an adaptive minimisation algorithm to intravenous balanced crystalloid solution (Plasma-Lyte 148) or saline during surgery and up until 48 h after transplantation. Trial fluids were supplied in identical bags and clinicians determined the fluid volume, rate, and time of discontinuation. The primary outcome was DGF, defined as receiving dialysis within 7 days after transplantation. All participants who consented and received a transplant were included in the intention-to-treat analysis of the primary outcome. Safety was analysed in all randomly assigned eligible participants who commenced surgery and received trial fluids, whether or not they received a transplant. This study is registered with Australian New Zealand Clinical Trials Registry, (ACTRN12617000358347), and ClinicalTrials.gov (NCT03829488). Between Jan 26, 2018, and Aug 10, 2020, 808 participants were randomly assigned to balanced crystalloid (n=404) or saline (n=404) and received a transplant (512 [63%] were male and 296 [37%] were female). One participant in the saline group withdrew before 7 days and was excluded, leaving 404 participants in the balanced crystalloid group and 403 in the saline group that were included in the primary analysis. DGF occurred in 121 (30%) of 404 participants in the balanced crystalloid group versus 160 (40%) of 403 in the saline group (adjusted relative risk 0·74 [95% CI 0·66 to 0·84; p<0·0001]; adjusted risk difference 10·1% [95% CI 3·5 to 16·6]). In the safety analysis, numbers of investigator-reported serious adverse events were similar in both groups, being reported in three (<1%) of 406 participants in the balanced crystalloid group versus five (1%) of 409 participants in the saline group (adjusted risk difference –0·5%, 95% CI –1·8 to 0·9; p=0·48). Among patients receiving a deceased donor kidney transplant, intravenous fluid therapy with balanced crystalloid solution reduced the incidence of DGF compared with saline. Balanced crystalloid solution should be the standard-of-care intravenous fluid used in deceased donor kidney transplantation. Medical Research Future Fund and National Health and Medical Research Council (Australia), Health Research Council (New Zealand), Royal Australasian College of Physicians, and Baxter.